Fundamental solution of the time-fractional telegraph Dirac operator - Ferreira, Milton dos Santos (2017)
In this work we obtain the fundamental solution (FS) of the multidimensional time-fractional telegraph Dirac operator where the two time-fractional derivatives of orders $α \in ]0,1]$ and $β \in ]1,2]$ are in the Caputo sense. Explicit integral and series representation of the FS are obtained for any dimension. We present and discuss some plots of the FS for some particular values of the dimension and of the fractional parameters $α$ and $β$. Finally, using the FS we study some Poisson and Cauchy problems.